Sex and transhumanism (Annals of the University of Bucharest. Philosophy Series, 2025)
In this article, the transhumanist project is analyzed through the lens of one of the phenomena characterizing human existence, i.e. sex. The aim of the article is to reconstruct the ontological structure of transhumanism employing the reflection on the phenomenon of sex and, based on this reconstruction, to prepare the conceptual fundament for the most theoretically justified ethical treatment of the transhumanist project. The genealogical studies by Michel Foucault and historical-ontological research by Ian Hacking are used as the theoretical basis and methodological guideline for the analysis carried out in the article. The analysis demonstrates that due to the ontologically ‘mobile’ nature of the main object of transhumanism (the human), transhumanism itself unfolds as a project that is constantly shifting in terms of its purposes and goals. Therefore, transhumanism is a project that cannot be realized in practice in principle. The impossibility of realizing the transhumanist project, consequently provides an ethically engaged treatment thereof. The article is concluded by stating transhumanism to be a nihilistic ideology – or, paradoxically, an ideology without an ideal – which actually does not manifest as the improvement of the human, but only as their perpetual identity and anthropological remaking based on new ever emerging techno-scientific capabilities.
Keywords: transhumanism; sex; science; technology; Foucault; Hacking